2009
DOI: 10.1212/wnl.0b013e3181b04b24
|View full text |Cite
|
Sign up to set email alerts
|

Conflict monitoring in early frontotemporal dementia

Abstract: Background: Despite the extensive frontal atrophy and behavioral disinhibition that characterizes

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 39 publications
2
32
0
1
Order By: Relevance
“…Patients who showed impaired values on 2 or more scores were classified as having impaired neuropsychological performance (INP group). Similar procedures for classifying ‘high’- and ‘low’-performance bvFTD patients have previously been reported in the literature [1]. Preliminary analysis revealed that all participants originally recruited for the control group had normal neuropsychological performance, which is why they were all clustered into a unique control group (CTR).…”
Section: Methodsmentioning
confidence: 88%
See 1 more Smart Citation
“…Patients who showed impaired values on 2 or more scores were classified as having impaired neuropsychological performance (INP group). Similar procedures for classifying ‘high’- and ‘low’-performance bvFTD patients have previously been reported in the literature [1]. Preliminary analysis revealed that all participants originally recruited for the control group had normal neuropsychological performance, which is why they were all clustered into a unique control group (CTR).…”
Section: Methodsmentioning
confidence: 88%
“…In clinical practice, it is not uncommon to find early behavioral-variant frontotemporal dementia (bvFTD) patients who, to a considerable extent, are intellectually unimpaired [1,2], while relatives and caregivers depict a strikingly different picture: they claim that these patients show severe changes in their behavior and real-life decision-making skills. Although patients with frontal lobe damage usually maintain normal intellectual functioning, they develop difficulties in planning workday and future events, and in choosing friends, partners and activities, and their actions frequently lead to diverse losses in terms of financial status and social standing [3].…”
Section: Introductionmentioning
confidence: 99%
“…Patients were dichotomized into those who scored within normal limits on standard tasks of executive function and those who did not, and their scores on the Flanker task were compared. Interestingly, both bvFTD patient groups showed a signi fi cantly larger congruency effect (e.g., longer latency on incongruent vs. congruent trials) compared to the normal control subjects [ 93 ] . These results suggest that even those patients who perform well on standard tasks of executive function may still have subtle, yet perceptible de fi cits in cognitive control, if measured by the appropriate method.…”
Section: Attention/executive Functions In Bvftdmentioning
confidence: 89%
“…Investigation of this domain using "traditional" tasks of executive function has led to largely con fl icting fi ndings. While some studies fi nd impairments in this domain [ 71,[91][92][93] , others do not [94][95][96] . One reason for this discrepancy likely relates to stage of disease at which patients are assessed.…”
Section: Attention/executive Functions In Bvftdmentioning
confidence: 98%
See 1 more Smart Citation